Notification System for Sale on Video Games using Social Media Mining - Naman Phadnis, Aswathy Gopalakrishnan, Chanchal Matania (International Journal of Advanced Science and Technology, 2020)
This paper aims to identify video games currently on sale and notify users who have shown interest in them, which is done by tracking their social media usage patterns. It keeps a record of their activity content online with the help of text mining, which is then filtered and interpreted to determine the user’s inclination to gaming and purchasing particular video games. The data derived from different users in different platforms can be transformed into event logs for text mining techniques to identify future trends in the interests of the users. With the help of natural language processing, the system will take human input and produce computer-oriented output. NLP performs a linguistic analysis that helps a machine to read the text. This system ultimately facilitates buying video games by incorporating various components of text mining. Keywords: Video games, Notification System, Sale Identification, Social Media, User Pattern, Text Recognition, Process Mining.